Adoption of Good Beekeeping Practices Among Beekeepers in Chitwan District, Nepal - Sharma, Nishma Kriti; KC, Prabin; Mishra, Binayak Prakash (Nepalese Journal of Agricultural Sciences, 2026)
The adoption of Good Beekeeping Practices is widely recognized as essential for enhancing productivity, sustainability, and commercial success in the beekeeping industry. In Nepal, despite the sector’s strong potential to support rural livelihoods, its growth remains constrained by reliance on traditional methods. This study investigates the extent of Good Beekeeping Practices adoption and explores the socioeconomic factors influencing their use among beekeepers in Chitwan, one of the country’s leading honey producing districts. A mixed-methods approach was employed, combining a survey of 57 randomly selected beekeepers with qualitative insights from focus group discussions and key informant interviews conducted within the Prime Minister Agriculture Modernization Project (PMAMP) area. Data were analyzed using descriptive statistics and a binary logit regression model. Findings reveal a 59.6% adoption rate of Good Beekeeping Practices. Core practices such as the use of protective gear, appropriate apiary site selection, and maintenance of colony handling (64.9%) and feeding honey-pollen mixture (52.6%) were less common. Regression results indicate that age and the number of beehives negatively influenced adoption, whereas annual income from beekeeping, off-farm income, and honey production were positive and significant. The study concludes that financial capacity and economic resilience are key to encouraging the adoption of better practices. It suggests that efforts to increase profitability and diversify income are essential for modernizing the sector.